Analisis Kesiapsiagaan Pada Unit Pelaksanaan Teknis Penanggulangan Bencana Daerah IV Balikpapan - Noeryanto, Noeryanto; Siboro, Impol; Marpaung, Rotua Catrina (IDENTIFIKASI, 2022)
Fire is an unwanted disaster that can cause losses from various parties and can also cost many lives. Fire disasters must be managed properly and planned and there must be an emergency response system in handling fires. Fire prevention can be realized by establishing a fire emergency response system, education on fire prevention, fire prevention procedures, and fire training. This study aims to determine the extent to which firefighters are prepared. The benefits of research provide input as material for evaluation and consideration in efforts to prevent accidents and work-related health problems. The research method is descriptive qualitative with observation and interview data collection techniques. The research location is at BPBD UPT PBD South Balikpapan. The results of this study can be concluded that the preparedness of existing officers is good, it can be seen from the existing organizational structure and the existing emergency response system there is a mismatch, from the observations made of preparedness decreasing due to the covid pandemic which causes training that should be carried out regularly. has periodically become hampered in recent months. The qualification standards of firefighters in this place also have a significant discrepancy, the average conformity with the qualification standards of firefighters has a value of 76%.